HISTORIOGRAFI ANTIK DAN HISTORIOGRAFI KRISTEN - Situmorang, Sihol (LOGOS, 2005)
Human being is a historical being. In the history the details of life and their struggle is expressed. For the people who believe in God, faith is a fundamental part in their life. The faith is experienced in the history and therefore the faithful see the history as an implementation of divine providence. Accordingly, explaining the history is an important task. The writers of the ancient history use the literary genres such as historiography, chronography and biography. In ancient christianity, the historical writers give a new meaning to the existing literatures. Their authority is not based on the divine inspiration but on the truth about salvific eschatological event. Eusebius is one of the pioneers of the ecclesiastical historiography. In the history of the Church it is the Divine Providence who guides and decides the course of all events to their ultimate purpose namely to prepare the Kingdom of God. Thus the history of the Church is a divine-spiritual history. Nowadays, the influence of Greek and Roman philosophers and famous writers is well observed especially in political theology. This new history is presented with the documentation which was unusual for the history of politics, but which was common in polemical works and biography.